INFLUENCE OF PRE-KILLING LIVING WEIGHT ON THE QUALITY OF CARCASES OF HYBRID PIGS IN THE CONDITIONS OF INDUSTRIAL PORK PRODUCTION IN UKRAINE - Mykola POVOD; Oksana KRAVCHENKO; Andriy GETYA; Valeriy ZHMAILOV; Olekasndr MYKHALKO; Olga KORZH; Tatiana KODAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The optimal pre-slaughter live weight of pigs for fattening in the conditions of an industrial pig complex in Ukraine was determined and its influence on the quality of pig carcasses was investigated. For the study, 80 heads of young pigs were selected, of which 32 were pigs and 48 were boars. Boars were surgically castrated at the age of 2 days. During fattening, all animals had free access to food and water. Pigs were fattened in group pens for 20-25 heads on a completely slotted floor. Feeding was carried out with complete feed of own production in the wet type. When the animals reached the age of 170 days, depending on live weight, they were divided into 3 groups: Group I - 85-95 kg; Group II - 100-110 kg, Group III - 115-120 kg and slaughtered at the meat plant. The results of slaughter were used to determine the main slaughter characteristics of pigs in accordance with generally accepted methods. After measurement, the carcasses were cut into pieces and evaluated for the yield of lean pork by deboning. As a result of the study, it was found that with the increase of ante-mortem live weight, the carcass yield of carcasses also increased. In all weight groups, pigs outnumbered boars in slaughter yield. At the same time, pig carcasses lost more weight during cooling compared to castrates (0.2-0.4%). The carcasses of castrated animals had a thicker fat, measured at different points on the carcass (0.1 to 3.6 mm above the first thoracic vertebra and 0.8 to 3.3 mm above 6-7 thoracic vertebrae). Further analysis of the carcasses showed that the ratio of valuable parts of carcasses does not change significantly with increasing pre-slaughter live weight of animals. The mass fraction of tenderloin, neck, shoulder, loin and ham was higher in pig carcasses, while in castrates only the proportion of brisket was higher. In general, the weight of meat from the four main cuts in pigs was significantly higher than in castrates (group I - 58.4 against 52.2%; group II - 56.6 against 55.5%; group III - 58.3 against 56.6%). Analysis of the morphological composition of the carcasses showed an increase in meat content with increasing pre-slaughter live weight. In particular, in animals with a live weight of 115-120 kg, the proportion of meat in the carcass was 68.6 ± 0.34 in castrates and 71.0 ± 0.59% in pigs.